Advances in the synthesis of three-dimensional molecular architectures by dearomatizing photocycloadditions. (1st January 2022) - Oderinde, Martins S.; Jin, Soomin; Dhar, T.G. Murali; Meanwell, Nicholas A.; Mathur, Arvind; Kempson, James
Abstract: The dearomatizing photocycloaddition reaction is a powerful and effective strategy for synthesizing complex, three-dimensional, polycyclic scaffolds from simple aromatic precursors. Generally, the dearomatizing photocycloaddition reaction is promoted by visible light and occurs via an energy transfer (EnT) process. This mini-review provides an overview of recent advances in this area (2018–2020), encompassing both intramolecular and intermolecular transformations. While the majority of the studies are centered on intramolecular processes due to their predictable regio- and stereo-selectivity, intermolecular transformations that show an exceptionally broad substrate scope are beginning to emerge. Graphical abstract: Image 1 Highlights: Recent advances in dearomatizing photocycloadditions. Photocycloaddition reactions of heterocycles. Synthesis of sp 3 -rich three-dimensional molecular architectures. Energy transfer promoted [2 + 2] cycloaddition. Visible-light [2 + 2] cycloaddition reactions.